Diesel to Dual Fuel Conversion Process Development - Bhavani, Kompalli; Murugesan, Sivanesan (International Journal of Engineering and Technology, 2018)
This paper aims to develop a process for conversion of Diesel Engine for Dual Fuel operation which is basically designed to reduce the economic costs and pollutant Emissions. The increasing cost of Diesel Fuel leads to the necessity of an Alternate fuel, i.e Compressed Natural gas (CNG). Â In this research a 16 cylinder, 50.25liter, Turbocharged After cooler V-shaped Engine is used for the conversion into Dual Fuel Engine. Dual fuel engine can be operated on both Diesel and CNG modes simultaneously. In this Engine the Air and CNG are mixed in required ratios in an Air- Gas mixer and the mixture is injected into the Combustion chamber. As Gaseous fuel CNG cannot self-ignite itself because of its high Auto ignition temperature a required amount of Diesel is injected into the Combustion Chamber at the end of compression stroke for ignition purpose which is known as Secondary fuel or a PILOTFUEL. This paper tries to show the process development of converting Diesel Engine for dual fuel operation on multiple platforms.Â